Antibody-Mediated Rejection in Kidney Transplantation: A Review. (10th April 2012) - Puttarajappa, Chethan; Shapiro, Ron; Tan, Henkie P.
Abstract : Antibody mediated rejection (AMR) poses a significant and continued challenge for long term graft survival in kidney transplantation. However, in the recent years, there has emerged an increased understanding of the varied manifestations of the antibody mediated processes in kidney transplantation. In this article, we briefly discuss the various histopathological and clinical manifestations of AMRs, along with describing the techniques and methods which have made it easier to define and diagnose these rejections. We also review the emerging issues of C4d negative AMR, its significance in long term allograft survival and provide a brief summary of the current management strategies for managing AMRs in kidney transplantation.